APLIKASI PROGRAM QUALITY CONTROL BARANG UNTUK MENUNJANG PELAPORAN PADA BAGIAN TEKNIK PERGURUAN TINGGI RAHARJA - Aris Aris; Tiya Puspita Firdaus; Neha Nurseha (UNIVERSITAS RAHARJA, 2018)
Data processing system of Higher Education Raharja needs the best and integrated to facilitate decision making and create good service standard. Especially if the data is related to Control and Quality. Data and information easily accessible to support the performance of each section. As in theEngineering section, In data processing Engineering section still can not provide the best service to meet the strategic information needs required to support reporting on the management of Higher Education Raharja. It takes a long time to generate information data items as required, this happens because it has not been integrated with the management and information processing can not be effective and efficient, With the design method using UML, as well as making the application program using PHP programming language website based .So can help in reporting data goods engineering section for management that can improve the performance of engineering section for Higher Education Raharja so as to provide good and faster service.